Palmitoylation controls trafficking of the intracellular Ca2+ channel MCOLN3/TRPML3 to regulate autophagy. Issue 2 (1st February 2019) - Kim, So Woon; Kim, Dong Hyun; Park, Kyoung Sun; Kim, Mi Kyung; Park, Yun Min; Muallem, Shmuel; So, Insuk; Kim, Hyun Jin
ABSTRACT: MCOLN3/TRPML3 is a Ca 2+ -permeable cation channel that is expressed in multiple subcellular compartments with dynamic localization. Our previous studies suggest that upon macroautophagy/autophagy induction MCOLN3/TRPML3 is recruited and provides Ca 2+ for the fusion process in autophagosome biogenesis. However, how intracellular trafficking and the Ca 2+ channel function of MCOLN3/TRPML3 are related to autophagy are not known. Here we report that MCOLN3/TRPML3 undergoes palmitoylation at its C-terminal region, which is required for dynamic trafficking and cellular function of MCOLN3/TRPML3 in autophagy. Palmitoylation regulated MCOLN3/TRPML3 surface expression and trafficking, but not channel properties or localization and function of intracellular MCOLN3/TRPML3. Activation of intracellular MCOLN3/TRPML3 induced robust Ca 2+ release, which solely increased autophagy in Ca 2+ - and palmitoylation-dependent manners. Palmitoylation regulated not only intracellular MCOLN3/TRPML3 trafficking to autophagic structures but also autophagic flux in induced autophagy. Importantly, nutrient starvation activated MCOLN3/TRPML3 to release Ca 2+ and increased the level of MCOLN3/TRPML3 palmitoylation. Disruption of MCOLN3/TRPML3 palmitoylation, however, abolished the starvation-induced MCOLN3/TRPML3 activation without affecting channel activity. These results suggest that trafficking and channel function of MCOLN3/TRPML3 are regulated in the context of autophagy, and palmitoylation is a prerequisite for the function of MCOLN3/TRPML3 as a Ca 2+ channel in autophagosome formation by controlling its trafficking between subcellular compartments. Abbreviations : 17-ODYA, 17-octadecynoic acid; 2-BP, 2-bromopalmitate; BFA, brefeldin A; DN, dominant-negative; GPN, glycyl-L-phenylalanine-beta-naphthylamide; HN, hydroxylamine; KD, knockdown; MCOLN3/TRPML3, mucolipin 3; MS, mass spectrometry; PAT, palmitoyl acyltransferase; PM, plasma membrane; WT, wild type; ZDHHC, a zinc-finger motif and an Asp-His-His-Cys sequence